The Building of a Business Community: Focus on a University-Based Incubator - Rawlingson, Sam (2018)
Abstract This study has investigated the building of business communities within university-based incubators (UBI) and provided a map of how a UBI Community is built. The interviews conducted with the incubator’s members and management gave a clear picture of the elements at stake in and outside the facility. As a result, the study identified external and internal pillars which pinnacle the building of a UBI Community. The external pillars create the settings within which the internal pillars exist. The internal pillars are called Socialisation Mechanisms, Bottom-Up Support System and People-Oriented Ecosystem. The study argues that a UBI Community is being built by its members in a bottom-up approach, with top-bottom managerial guidance. The study also found that the pillars are interconnected and presented them in order of appearance for the UBI members, who need the Socialisation Mechanisms to be able to partake in the Bottom-Up Support System. The People-Oriented Ecosystem is the backbone of a UBI Community and acts as a mind-set setter for both management and members. Finally, while this study first tried to map the building of a UBI entrepreneurial ecosystem, the amount of data and the level of clarity required narrowed the focus of this study down to the mapping of a UBI Community. As a result, this study suggests the possibility of a UBI Community being identified as a pillar of the UBI entrepreneurial ecosystem, along with notions of sustainability discussed in the Appendix section. This however is for further research to explore as the main discovering of this study remains the mapping of a UBI Community.